MEDAN MAKNA RASA SAKIT DALAM BAHASA MELAYU DIALEK SAMBAS - Jayanti, Jayanti; Patriantoro, Patriantoro; Muzammil, Ahmad Rabi?ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract.This research focuses on the semantic field that discusses observations on the members of the human body, namely about pain in the Sambas dialect Malay, precisely in the District of Paloh. learning Indonesian in junior high school VII. The method used in this research is descriptive method with a qualitative research form. The data and data sources in this study are in the Sambas dialect Malay spoken by the informant. The data collection technique used by researchers is to go directly to the field. In addition, the technique to test the validity of the data used is the perseverance of observation, the adequacy of references, and guidance with lecturers using data analysis techniques which are based on research problems of the meaning of pain in the Sambas dialect Malay. Based on the results of this study found 37 descriptions of lexemes, 37 descriptions of lexical meanings and 15 meanings of collocation. In addition, this research is expected to be used as teaching material in learning Indonesian curriculum 2013 in the seventh grade junior high school. Keywords: Field Of Meaning, Lexeme, Lexical, Collocation